2012
DOI: 10.1186/1471-2318-12-56
|View full text |Cite
|
Sign up to set email alerts
|

Comparing frailty measures in their ability to predict adverse outcome among older residents of assisted living

Abstract: BackgroundFew studies have directly compared the competing approaches to identifying frailty in more vulnerable older populations. We examined the ability of two versions of a frailty index (43 vs. 83 items), the Cardiovascular Health Study (CHS) frailty criteria, and the CHESS scale to accurately predict the occurrence of three outcomes among Assisted Living (AL) residents followed over one year.MethodsThe three frailty measures and the CHESS scale were derived from assessment items completed among 1,066 AL r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
103
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(124 citation statements)
references
References 32 publications
10
103
1
1
Order By: Relevance
“…The absence of a universal criterion accepted by researchers to evaluate frailty prevents the comparison between different studies, because the publications use different instruments (Frailty Index, Cardiovascular Health Study, Armstrong Index, FI-CGA) (22)(23)(24) . A systematic review, between 1990 and 2010 (23) , investigated the association between geriatric syndromes (including frailty) and hospitalization and admission to long term care facilities, with various definitions of frailty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of a universal criterion accepted by researchers to evaluate frailty prevents the comparison between different studies, because the publications use different instruments (Frailty Index, Cardiovascular Health Study, Armstrong Index, FI-CGA) (22)(23)(24) . A systematic review, between 1990 and 2010 (23) , investigated the association between geriatric syndromes (including frailty) and hospitalization and admission to long term care facilities, with various definitions of frailty.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the different stages of frailty, measured with different instruments, association between frailty, death, hospitalization and institutionalization were established. The authors report that residents with more severe levels of frailty are more likely to die, become hospitalized, and require institutionalization in long-term care facilities (22) . A prospective cohort study involving 752 elderly, aged 75 years or older, to investigate the predictive validity of the frailty index based on the geriatric assessment (CGA-FI) found that the increase of values in the index was associated with the growth of the risk of death, institutionalization, and length of hospital stay (24) .…”
Section: Study Financed By Fundação De Amparo à Pesquisa Do Estado Dementioning
confidence: 99%
“…Persons without any of these frailty symptoms were considered as robust (the reference group). The Cardiovascular Health Study criteria for frailty have been widely used in the literature and have good predictive validity for adverse health outcomes [1]. …”
Section: Methodsmentioning
confidence: 99%
“…Frailty is considered an age-associated syndrome that leads to difficulties in daily activities and increased risk for institutionalization and mortality [1]. According to the definition by Fried et al [2], frailty is characterized by several physical symptoms, including weight loss, exhaustion, poor hand-grip strength, slow walking speed and physical inactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Aged care homes have grown rapidly [3]. Compared to their community counterparts, aged care home residents appear to be frailer, with higher rates of illness and disability [4,5]. In a medical context, frailty is defined as a syndrome of diminished strength or endurance, and reduced physiologic function that increases an individual's vulnerability to various stressors [6].…”
Section: Introductionmentioning
confidence: 99%